Evaluasi Formulasi Sediaan Floating Mikroenkapsulasi yang Mengandung Ekstrak Etanol Kunyit Putih (Curcuma Zedoaria Rosc.) - Rika Mai Dinasari Br Sembiring; Razoki Razoki; Erida Novriani; Hariyadi Dharmawan Syahputra (Pusat Riset dan Inovasi Nasional, 2025)
This test aims to evaluate the formulation of floating microcapsule preparations containing ethanol extract of white turmeric (Curcuma zedoaria Rosc.), using chitosan, sodium alginate, and calcium chloride polymers as crosslinking agents. The preparation was formulated using the crosslinking method and tested based on its physical properties, which include moisture content, physical stability through cycle tests, resistance to the gastric and intestinal mucosa. The results showed that the microcapsule formulation was able to maintain the color and texture during the storage period well. The microcapsule durability test showed that the particles could survive in the gastric and intestinal mucosa for two hours. In addition, the water content is within the range that is in accordance with the requirements, namely, at a concentration of 0.25% there is (22%), a concentration of 0.5% there is (38.75%), a concentration of 0.75% there is (22.5%), and the blank has 20.5% water content. Based on previous research by Mardikasari et al., (2020) which used chitosan and alginate polymers. Through this method, this formulation shows the possibility as a technology-based drug delivery system that survives effectively in increasing the bioavailability of active substances from white turmeric.